Exploring psychiatric comorbidities and their effects on quality of life in patients with temporal lobe epilepsy and juvenile myoclonic epilepsy. Issue 4 (8th February 2017) - Ertem, Devrimsel H.; Dirican, Ayten C.; Aydın, Agah; Baybas, Sevim; Sözmen, Vedat; Ozturk, Musa; Altunkaynak, Yavuz
Abstract : Aim: The relation of epilepsy with psychiatric disorders is of great interest to researchers due to its behavioral, social, and cognitive outcomes. In this study, we explored psychiatric comorbidity and its effects on quality of life (QOL) in patients with mesial temporal lobe epilepsy (MTLE) and juvenile myoclonic epilepsy (JME). Methods: Thirty patients with MTLE, 30 patients with JME, and 30 healthy controls underwent the Structured Clinical Interview for DSM‐IV (SCID‐I) to diagnose psychiatric disorders. None of the subjects had previously undergone psychiatric examination. The Quality of Life in Epilepsy Inventory‐89 (QOLIE‐89) was used to assess QOL. We compared psychiatric comorbidity among groups and evaluated its effects on QOL. Results: We detected comorbid psychiatric disorders in 37% of patients with JME and in 57% of patients with MTLE. Comorbid psychiatric disorders were less frequent in healthy controls compared to the patient groups ( P = 0.029). Comparing demographic and clinical features of patients with JME and MTLE and their mean QOL scores, there was no statistical difference. Furthermore, we compared QOLIE scores between patients with and without psychiatric comorbidity. JME patients with mood disorders had lower scores on the Attention/Concentration subscale ( P = 0.013). MTLE patients with a psychotic disorder had lower scores on the Social Isolation, Energy, and Fatigue subscales ( P = 0.045). Patients with somatoform disorders had higher Pain scores ( P = 0.04). Conclusion: Our study suggests that comorbid psychiatric disorders negatively affect patients' QOL regardless of seizure syndrome. Comorbid psychiatric conditions should be determined to increase QOL in patients with epilepsy.